IDEAL PRIMA FUZZY NEAR-RING - Saman Abdurrahman; Na'imah Hijriati; Thresye Thresye (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2013)
We discuss the prime ideal of near-ring, fuzzy prime ideal of near-ring whichincludes the relationship between prime ideal of near-ring and fuzzy prime ideal of near-ring.